2004
DOI: 10.1007/s00248-003-0004-4
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Communities Associated with Electrodes Harvesting Electricity from a Variety of Aquatic Sediments

Abstract: The microbial communities associated with electrodes from underwater fuel cells harvesting electricity from five different aquatic sediments were investigated. Three fuel cells were constructed with marine, salt-marsh, or freshwater sediments incubated in the laboratory. Fuel cells were also deployed in the field in salt marsh sediments in New Jersey and estuarine sediments in Oregon, USA. All of the sediments produced comparable amounts of power. Analysis of 16S rRNA gene sequences after 3-7 months of incubat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

20
318
3
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 453 publications
(346 citation statements)
references
References 63 publications
20
318
3
5
Order By: Relevance
“…'Geopsychrobacter electrodophilus' A2, 'Geopsychrobacter multivorans' A1 and Desulfuromusa sp. strain S1 were isolated from the surface of a current-harvesting electrode in a marine fuel cell (Holmes et al, 2004). Geobacter hydrogenophilus DSM 13691 T and Geobacter chapellei DSM 13688 T were obtained from the laboratory of John Coates.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…'Geopsychrobacter electrodophilus' A2, 'Geopsychrobacter multivorans' A1 and Desulfuromusa sp. strain S1 were isolated from the surface of a current-harvesting electrode in a marine fuel cell (Holmes et al, 2004). Geobacter hydrogenophilus DSM 13691 T and Geobacter chapellei DSM 13688 T were obtained from the laboratory of John Coates.…”
Section: Methodsmentioning
confidence: 99%
“…Desulfuromusa sp. strain S1, 'Geopsychrobacter electrodophilus' A2 and 'Geopsychrobacter multivorans' A1 were grown at 20 uC in APW medium (Coates et al, 1995) with Fe(III) oxide (60 mM) or colloidal S 0 (10 mM) as electron acceptor and acetate (5 mM) as electron donor (Holmes et al, 2004). Malonomonas rubra was grown in APW medium (Coates et al, 1995) with 40 mM fumarate, 40 % of the recommended amount of MgCl 2 .6H 2 O and CaCl 2 .2H 2 O and 0?36 g NaS.9H 2 O l 21 as reductant.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed studies of their metabolism have revealed them to be capable of bioremediation of several heavy metals, including uranium, plutonium, technetium, and vanadium, as well as biodegradation of several organic contaminants, including monoaromatic hydrocarbons (16,17,26). More recently, Geobacter species have been used to generate electricity from waste organic matter (2,15,19). These unique metabolisms make Geobacter species important players in the contaminated subsurface environment (18).…”
mentioning
confidence: 99%
“…These have often occupied more than half the volume of the implantable device [9] and consequently alternative means of power sources that may offer higher energy densities or lifetimes have been considered. Energy harvesters based on vibration [10,11], thermal gradients [12,13] and exogeneous chemicals [14,15] have therefore emerged as the most promising candidates. In this respect, the use of glucose and dissolved oxygen (DO) may hold the best promise of a long term energy supply for electronic implants due to their relative abundance in all tissues and their limited-dependency to ambient factors.…”
Section: Introductionmentioning
confidence: 99%